PENGGUNAAN GPS UNTUK MENDETEKSI PENYEBARAN PENYAKIT TUNGRO PADA DUA MUSIM TANAM PADI DI KECAMATAN POCO RANAKA TIMUR KABUPATEN MANGGARAI TIMUR PROPINSI NUSA TENGGARA TIMUR - Rulianus Boskosar; Sri Wahyuni (Agriculture Faculty of Flores University, 2019)
This study aims to determine the spread of Tungro disease in the Poco Ranaka Timur District, East Manggarai Regency, and how the development of Tungro disease in each location attacked. Data were analyzed descriptively and based on direct observations obtained in the field. Observation parameters in the form of the presence and development of Tungro disease from each sample location. In the two rice growing seasons by counting the number of clumps attacked in each sample location. The results of the study at nine sample locations showed an increase in the spread of Tungro disease from the first planting season to the second planting season by an average of 27.29%. The highest growth in the range of Tungro disease occurring at the fifth sample location by 90.87%. The lowest at the sample location ninth by 9.09%.